EFEKTIVITAS PENERAPAN MODEL PjBL BERBANTUAN MEDIA CHROMEBOOK DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Yuningsih Yuningsih; Sri Yamtinah; Idam Ragil Widianto Atmojo (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This research aims to explore the impact of implementing a PjBl model assisted by Chromebook media on the critical thinking skills of elementary school students. Additionally, this study also aims to determine the role of learning motivation in supporting the improvement of critical thinking skills. The study also examines the combined effect of the PjBl model with Chromebook integration and learning motivation on the development of students' critical thinking abilities. Quasi-experimental with nonequivalent control group design is the method used in this study, which allows researchers to observe differences between groups without randomization. The results from the t-test indicated that the Chromebook -supported PjBl model significantly contributed to the improvement of students' critical thinking skills, with a calculated t-value of 4.670, which surpassed the table t-value of 1.691, and a significance level of 0.000, which was below the 0.05 threshold. Furthermore, the influence of learning motivation on critical thinking skills was also found to be significant, as indicated by a t-value of 3.137, which exceeded the table t-value (1.691), and a significance value of 0.004. Additionally, the two-way ANOVA analysis results demonstrated that the Chromebook -assisted PjBl model, learning motivation, and their interaction together had a substantial effect on enhancing students' critical thinking skills, as evidenced by the significance value (p) being below 0.05.